2021
DOI: 10.1123/ijsnem.2021-0085
|View full text |Cite
|
Sign up to set email alerts
|

A 5-Year Analysis of Weight Cycling Practices in a Male World Champion Professional Boxer: Potential Implications for Obesity and Cardiometabolic Disease

Abstract: Weight cycling is thought to increase the risk of obesity and cardiometabolic disease in nonathletic and athletic populations. However, the magnitude and frequency of weight cycling is not well characterized in elite athletes. To this end, we quantified the weight cycling practices of a male World Champion professional boxer competing at super middleweight (76.2 kg). Over a 5-year period comprising 11 contests, we assessed changes in body mass (n = 8 contests) and body composition (n = 6 contests) during the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Then, seven studies were included in meta-analyses thanks to raw data sent by the authors, conducting 32 the total number of studies included in the meta-analyses. 2,[11][12][13]16,38,39,41,43,53,[78][79][80][81][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100]…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, seven studies were included in meta-analyses thanks to raw data sent by the authors, conducting 32 the total number of studies included in the meta-analyses. 2,[11][12][13]16,38,39,41,43,53,[78][79][80][81][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100]…”
Section: Search Resultsmentioning
confidence: 99%
“…4 Combat sports athletes regained a mean of 5.5 ± 2.4% of BW WL . [2][3][4][11][12][13][14]38,40,41,43,44,50,53,67,71,78,79,[83][84][85][87][88][89][90][91][92][93][94][95]99,100,103 Pre-WL versus WG Among the 13 studies that reported apparent statistics regarding BW pre-WL versus BW WG , 8 did not notice any significant change (À0.49 ± 0.18 kg after 8.1 ± 8.7 days of WG), 43,63,85,87,88,[91][92][93] whereas 5 of them highlighted a significant decrease of BW (À1.36 ± 0.04 kg within 3.1 ± 3.4 days of WG, p < 0.05). 41,50,53,89,95 Four 41,50,…”
Section: Wl Methods and Wg Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that sleep may improve with subtle changes in TL but become disturbed with large increases relative to the athlete ( 19 ). Whilst the TL of combat sport athletes may not be as high compared to athletes from other sports ( 20 ), due to BM elevations induced partly from inactivity ( 5 , 21 ), these athletes are often exposed to a large increase in TL when making weight. This is supported by data in combat sport athletes, where sleep was rated worse during early preparation training compared with mid preparation training and on training days compared with rest days, indicating sleep may be challenged when commencing training after a rest period ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, findings show a considerable energy deficit over a period as short as 8-weeks can elicit an ad libitum energy intake of >36,000 kcal per week, resulting in a body mass gain of 8.3 kg (Langan- Evans et al, 2021). It is noted that such periods of hyperphagia are of particular concern to individuals predisposed to continually fluctuating energy intakes given the subsequent gain in body mass later in life (Saarni et al, 2006;Pietiläinen et al, 2011;Langan-Evans et al, 2021;Morehen et al, 2021).…”
Section: An Argument For Rebound Hyperphagiamentioning
confidence: 99%